2012
DOI: 10.4102/curationis.v35i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric nurse practitioners’ experiences of working with mental health care users presenting with acute symptoms

Abstract: Psychiatric nurse practitioners (PNPs) working with mental health care users presenting with acute symptoms work in a complex environment. This environment is characterised by mental health care users who may present with a history of violence, sexual assault and substance misuse. The objectives of this study were twofold: firstly, to explore and describe the experiences of PNPs working with mental health care users (MHCUs) presenting with acute symptoms; and secondly, to make recommendations for the advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…The importance of confidence in clinical decision-making and remaining calm in a crisis or other unplanned events has been identified across a range of healthcare settings (Cleary et al, 2012;Yang, Williams, & Fang, 2011;Yang et al, 2012). Research has clearly identified that this skill is important for mental health nurses (Cleary et al, 2011(Cleary et al, , 2012Dickinson et al, 2009;Edward, 2005;Ngako et al, 2012), although not described specifically in relation to the qualities of clinical leadership.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of confidence in clinical decision-making and remaining calm in a crisis or other unplanned events has been identified across a range of healthcare settings (Cleary et al, 2012;Yang, Williams, & Fang, 2011;Yang et al, 2012). Research has clearly identified that this skill is important for mental health nurses (Cleary et al, 2011(Cleary et al, , 2012Dickinson et al, 2009;Edward, 2005;Ngako et al, 2012), although not described specifically in relation to the qualities of clinical leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing environments that are unpredictable, such as emergency departments, intensive care units, and acute mental health settings (Cleary et al, 2011(Cleary et al, , 2012Currid, 2008;Gillespie, Gates, & Berry, 2013;Ngako, van Rensburg, & Mataboge, 2012;Nooryan, Gaspryan, Sharif, & Zoladl, 2011;Ward, 2011), require nurses to have specialist skills in their specialized area of nursing and to be confident in decisionmaking (Fry et al, 2013;Yang, Thompson, & Bland, 2012). In a medical intensive care unit, for example, nurses will need to have expertise in a number of clinical procedures that are more common in that setting, such as assessing levels of con-sciousness (Chan & Matter, 2013) or delirium monitoring (Balas et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the UK and other Western countries, adolescent inpatient care is becoming increasingly specialized as adolescents form a heterogeneous patient group with mixed disorders and multiple diagnoses (Ellil€ a et al 2007). However, often consumers of inpatient services display acute symptoms such as suicidal intentions, hallucinations, delusions and a risk of harm to themselves and others (Ngako et al 2012), generally resulting from experiences of trauma, emotional mistreatment, sexual abuse, neglect, loss, family discord, addiction, criminality and severe mental disorders (Van Sant & Patterson 2013). Consequently, adolescent mental health nursing staff represent a specialized cohort of healthcare professionals informing both the setting and population of this study.…”
Section: Introductionmentioning
confidence: 99%